Anti-cracking anti-aging high-shading PC (polycarbonate) composite material as well as preparation and application thereof

By using silicone copolymerized PC and hydroxysilicon modified MBS toughening agent in high-light shielding PC composite materials, combined with titanium dioxide for chloride, the stress cracking problem caused by rapid cooling in the prior art is solved, and the material is improved Weather resistance and light-shielding effect, suitable for plastic-clad aluminum products.

CN119119706APending Publication Date: 2024-12-13CGN TOXXON (XIAMEN) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411219132.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing high-blocking PC composite materials are too severe due to rapid cooling during processing, resulting in stress cracking of products after long-term use, and uneven weathering and mechanical properties.

Method used

Silicone copolymer PC resin and hydroxysilicon modified methacrylic-butadiene-styrene copolymer (MBS) as toughening agents, combined with chlorination process, optimize the dispersion effect and compatibility of the material Improve the light-shielding effect of the material and anti-cracking ability.

Benefits of technology

It significantly improves the impact strength and impact strength retention rate of the composite material, enhances the weather resistance and crack resistance of the material, solves the problems of poor internal residual stress and aging performance, and meets the application requirements of plastic-clad aluminum products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119706A_ABST
    Figure CN119119706A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-cracking anti-aging high-shading PC composite material, a preparation method thereof and application of the anti-cracking anti-aging high-shading PC composite material in manufacturing of plastic-coated aluminum products. The anti-cracking anti-aging high-shading PC composite material comprises the following raw materials in percentage by mass: 90-94% of PC resin, 2-6% of titanium dioxide and 2-6% of a toughening agent, the PC resin is siloxane copolymerized PC; the flexibilizer is a hydroxyl silicon modified methacrylic acid-butadiene-styrene copolymer. The preparation method comprises the following steps: uniformly mixing the raw materials, putting the mixture into a double-screw extruder, and carrying out melt mixing, plasticizing and extrusion to obtain the anti-cracking anti-aging high-shading PC composite material. The PC composite material is stable in performance, can be applied to plastic-coated aluminum products, and solves the problems of poor weather resistance, stress cracking and the like of the plastic-coated aluminum products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of light-shielding polycarbonate (PC) composite materials, and in particular to a crack-resistant, aging-resistant, high-light-shielding PC composite material and a preparation method and application thereof. Background Art

[0002] When the plastic-coated aluminum heat sink product was first launched in China, it overturned the traditional LED market's understanding of heat sinks, and was quickly accepted and applied by many companies in the market. This heat sink material uses high thermal conductivity plastic on the outer layer and aluminum on the inner layer, fully considering and combining the advantages of plastic and aluminum. Because of its plastic insulation performance, it can pass safety certification and improve safety performance. At the same time, this "plastic-coated aluminum" heat sink material is lower in cost than aluminum and can be recycled.

[0003] The molecular structure determines the polymer properties. The carbonyl group in PC can enhance the interaction between molecules, the ether bond improves the solubility in organic solutions, and the benzene ring can also reduce its solubility in solutions. However, due to the excellent heat resistance and long repeating units of the benzene ring, the glass transition temperature is high, the intermolecular force is large, the rigid chain segments are entangled with each other, and the molecular chain is difficult to slide. During the processing, the melt flows non-isothermally in the mold to form shear stress and normal stress. Due to the rapid drop in temperature, the molecular chain cannot be completely relaxed and is forced to orient. The residual stress is frozen in the material. When the plastic-coated aluminum product is in a harsh environment for a long time, the outer layer of PC is prone to cracking. Therefore, how to improve the mobility of the PC molecular chain and the aging resistance while filling with titanium dioxide has become the focus of researchers.

[0004] For example, Chinese patent application CN110041682A discloses a high-toughness and high-light-shielding PC, the material of which is filled with titanium dioxide (6-12%) to improve the reflectivity, and an acrylic impact modifier (3-5%) is added to reduce the adverse effects of titanium dioxide on the mechanical properties of PC. However, during the injection molding process, excessive titanium dioxide in a high-temperature barrel can easily induce partial degradation of PC, thereby resulting in uneven performance of PC products.

[0005] For example, Chinese patent application CN114213829A discloses a flame retardant high light-shielding PC, which uses PC resin, titanium dioxide, barium sulfate, compound flame retardant, and toughening agent in a weight ratio of 1000: (31-58): (14-30): (8-12): (20-40). Barium sulfate has good compatibility with PC, and compounding it with titanium dioxide can optimize the light-shielding performance of PC materials. However, the dispersibility of barium sulfate in the matrix is ​​unstable, and the intermolecular force is large. During injection molding, due to the rapid cooling of the material, each region drops from a higher temperature to the glass transition temperature at different times, and the internal residual thermal stress is excessive, and stress cracking will occur in the product after long-term use. Summary of the invention

[0006] In view of the above-mentioned technical problems and the shortcomings in the art, the present invention provides a crack-resistant, aging-resistant and high-light-shielding PC composite material and its preparation method and application. The PC composite material has stable performance and can be used in plastic-coated aluminum products to solve the problems of poor weather resistance and stress cracking.

[0007] The specific technical solutions are as follows:

[0008] In a first aspect, the present invention provides a crack-resistant, aging-resistant, high-light-shielding PC composite material, wherein the raw material composition comprises, by mass percentage:

[0009] PC resin 90% to 94%, such as 90.5%, 91%, 92%, 93.5%, etc.;

[0010] Titanium dioxide 2% to 6%, preferably 3% to 4%, more preferably 3.5%;

[0011] Toughener 2% to 6%, preferably 3% to 5%, more preferably 4%;

[0012] The PC resin is siloxane copolymerized PC;

[0013] The toughening agent is hydroxy silicon modified methacrylate-butadiene-styrene copolymer (MBS).

[0014] The PC resin of the present invention is siloxane copolymerized PC, contains flexible molecular chains with high viscoelasticity, and has good stability and mechanical properties.

[0015] The present invention uses hydroxysilicon-modified MBS as a toughening agent and adds it to the siloxane copolymer PC system, thereby ensuring the dispersion effect of titanium dioxide in the siloxane copolymer PC matrix, improving the interface compatibility, and significantly improving the light-shielding effect and anti-cracking ability of the composite material. The hydroxysilicon-modified methacrylate-butadiene-styrene copolymer contains siloxane segments, and these groups have excellent UV resistance. The siloxane group can effectively reduce the effect of photodegradation on the material under ultraviolet irradiation, thereby improving the weather resistance of PC. In addition, the introduction of the siloxane group increases the dynamic movement ability between molecules, so that the material can better adapt to deformation when subjected to external force, and the larger molecular freedom helps to disperse and reduce stress concentration, preventing the material from cracking due to stress concentration. The hydroxysilicon-modified MBS itself has good compatibility with the siloxane copolymer PC, and its introduction can also improve the compatibility between the siloxane copolymer PC and titanium dioxide.

[0016] The anti-cracking, aging-resistant and high-light-shielding PC composite material of the present invention has an impact strength greater than 63KJ / m 2The impact strength retention rate is not less than 75%, and it has a wide range of applications in plastic-coated aluminum products, lamp structural parts, etc.

[0017] The anti-cracking, aging-resistant and high-light-shielding PC composite material of the present invention has excellent weather resistance and anti-cracking ability, stable processing performance, meets the requirements for the outer layer material of plastic-coated aluminum lamps, and has insulation, light-shielding and heat dissipation functions, solving the problems of large internal residual stress, poor aging performance, uneven strength and the like of the current plastic-coated aluminum outer layer material.

[0018] The crack-resistant, aging-resistant and high-light-shielding PC composite material, the melt flow rate (MFR) of the PC resin at 300° C. and 1.2 kg is preferably 10 to 15 g / 10 min, and more preferably 10 to 12 g / 10 min.

[0019] In the crack-resistant, aging-resistant, high-light-shielding PC composite material, the mass proportion of siloxane in the siloxane copolymerized PC is preferably 5% to 10%, such as 6%. An appropriate siloxane ratio can balance the processing performance and the final product performance, which can not only ensure the melt stability, but also improve the toughness of the material.

[0020] The anti-cracking, aging-resistant, high-light-shielding PC composite material, the titanium dioxide is preferably a rutile titanium dioxide pigment produced by the chloride process. Chloride titanium dioxide has strong hiding power, strong light reflection ability, and can be evenly dispersed in the system, and is not easy to induce material degradation.

[0021] The anti-cracking, aging-resistant and high-light-shielding PC composite material, the mass content of TiO2 in the titanium dioxide is preferably above 95%, and further preferably above 96.5%.

[0022] In the crack-resistant, aging-resistant, high-light-shielding PC composite material, the particle size of the titanium dioxide is preferably 200 to 250 nm, and more preferably 220 to 240 nm. Titanium dioxide within this particle size range has a strong light scattering ability in the visible light band, can effectively absorb and scatter light, and improve the light-shielding ability of the composite material.

[0023] The crack-resistant, aging-resistant and high-light-shielding PC composite material, in the raw material composition, the mass percentage of the toughening agent is preferably 3% to 5%, and more preferably 4%. The obtained PC composite material has better impact strength and impact strength retention rate.

[0024] In some preferred examples, the anti-cracking, aging-resistant and high-light-shielding PC composite material, the PC resin is S1240T produced by Wanhua Chemical Group Co., Ltd., and the melt flow rate at 300° C. and 1.2 kg is 10 g / 10 min.

[0025] In some preferred examples, the anti-cracking, aging-resistant and high-light-shielding PC composite material, the titanium dioxide is CR210 of CITIC Titanium Co., Ltd., with a particle size of 230nm, wherein the mass content of TiO2 is 96.5%.

[0026] In some preferred examples, in the anti-cracking, aging-resistant and high light-shielding PC composite material, the toughening agent is UM-2270 produced by QuanSheng Polycarbonate Technology Co., Ltd.

[0027] The anti-cracking, aging-resistant and high-light-shielding PC composite material described in the first aspect may further include, by mass percentage, the following raw material composition:

[0028] Lubricant 0.1%~0.3%,

[0029] Antioxidant 0.1%~0.3%,

[0030] High temperature resistant additive 0.1%~0.3%.

[0031] The lubricant may include at least one of polyethylene wax, zinc stearate, pentaerythritol stearate, and the like.

[0032] The antioxidant may be a compound of a main antioxidant and a secondary antioxidant, wherein the main antioxidant may include at least one of antioxidant 1098, antioxidant 1076, etc., and the secondary antioxidant may include at least one of antioxidant 168, antioxidant 628, etc. Further, the mass ratio of the main antioxidant to the secondary antioxidant may be 1:1.

[0033] The high temperature resistant auxiliary agent may include at least one of epoxy grafted silicon acrylate core-shell polymer, diaryl secondary amine composition and the like.

[0034] In some embodiments, the high temperature resistant auxiliary agent may be a high molecular polymer having an epoxy functional group, and may include at least one of epoxy grafted silicone acrylate core-shell polymer, acrylonitrile-styrene-glycidyl ester copolymer, and the like.

[0035] In a second aspect, the present invention provides a method for preparing the anti-cracking, aging-resistant and high-light-shielding PC composite material according to the first aspect, comprising:

[0036] The raw materials are mixed and then put into a twin-screw extruder for melting, mixing, plasticizing and extrusion to obtain the anti-cracking, aging-resistant and high light-shielding PC composite material.

[0037] The temperature of the twin-screw extruder is preferably controlled at 220-240° C. Within this temperature range, the PC composite material system of the present invention has good fluidity and solubility, the processing process is more stable, it is beneficial to form a uniform product, and the problems that may occur during the processing are reduced.

[0038] The screw length-to-diameter ratio of the twin-screw extruder may be 36 to 40:1.

[0039] The main engine speed of the twin-screw extruder can be 350-400 rpm.

[0040] In a third aspect, the present invention provides an application of the anti-cracking, aging-resistant, high-light-shielding PC composite material described in the first aspect in the manufacture of plastic-coated aluminum products. Furthermore, the plastic-coated aluminum product can be a structural part of a lamp (including an LED downlight or other lamps, etc.), which has a high heat dissipation capacity and can also increase the service life of the finished lamp.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. Siloxane copolymer PC is used, and the siloxane group has a high chemical stability. The Si-O bond between the silicon atom and the oxygen atom in the siloxane structure has a very strong bonding ability. Compared with the CC or CO bond in hydrocarbons, the chemical stability of Si-O is higher, so the siloxane group has a strong tolerance to chemicals such as acids, alkalis, and solvents. At the same time, the reaction rate of the siloxane group with water is slow, and the generated silicate is relatively stable, which reduces the negative impact of hydrolysis on material properties.

[0043] 2. Titanium dioxide produced by the chlorination process has good UV shielding properties, which can block the degradation of PC by UV rays and reduce the photoaging of materials. It helps to extend the service life of PC and improve the surface properties of PC, making it more wear-resistant.

[0044] 3. The siloxane groups in the hydroxysilicon-modified methacrylic acid-butadiene-styrene copolymer toughening agent can improve the compatibility between siloxane copolymer PC and titanium dioxide, reduce the interface defects caused by the mismatch between filler and matrix, and -(-Si-O-Si-O-) n Compared with traditional carbon-based segments, the -segments have greater flexibility and can better absorb and buffer external stress, reducing the formation of stress concentration areas and thus reducing the risk of cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The following are photos of stress cracking of the color plates of Comparative Examples 1 to 4 and Examples 1 to 5. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0047] The performance test standards and methods are as follows:

[0048] Tensile strength: measured according to GB / T1040.2-2006, test conditions: temperature 23°C, air humidity 50%, tensile speed, 50mm / min;

[0049] Izod notched impact strength: According to GB / T 1843 standard test conditions, temperature 23°C, 50% air humidity;

[0050] Bending strength and bending modulus: According to GB / T 9341 standard test conditions: temperature 23°C, air humidity 50%, displacement speed, 50mm / min;

[0051] Melt mass flow rate: Test conditions: temperature 300°C, weight, 1200g;

[0052] High temperature aging test: put the injection molded standard test specimens into a 120℃ constant temperature aging box for 240h, take them out and cool them to 23℃, and test them according to GB / T 1843 standard;

[0053] Impact strength retention rate: Impact strength retention rate = impact strength (after high temperature aging test) / original impact strength × 100%;

[0054] Solvent resistance (carbon tetrachloride) test: Soak the molded color plate in 99.9% analytical pure carbon tetrachloride for 10 minutes, then put it in a constant temperature and humidity chamber for 18 hours, set the temperature to 85°C and the relative humidity to 85%. After cooling to 23°C, take a photo and observe the cracking of the color plate;

[0055] Light transmittance test: According to GB / T2410-2008 standard, the test specimen is 53mm long, 23mm wide and 1mm thick.

[0056] Each embodiment and comparative example is injection molded into corresponding standard specimens according to standard requirements and tested.

[0057] The raw materials used in the embodiments and comparative examples of the present invention are as follows:

[0058] PC resin: S1240T (siloxane copolymer PC, of ​​which the mass proportion of siloxane is 6%, MFR at 300°C and 1.2Kg is 10g / 10min), A1220 (siloxane-free, MFR at 300°C and 1.2Kg is 20g / 10min), 1100-0000 (siloxane-free, MFR at 300°C and 1.2Kg is 10g / 10min), Wanhua Chemical Group Co., Ltd.

[0059] Titanium dioxide: CR210 (particle size 230nm, TiO2 mass content 96.5%), CR211 (particle size 200nm, TiO2 mass content 94.5%), CITIC Titanium Co., Ltd.

[0060] Toughening agent: M722 (MBS toughening agent without hydroxyl silicon modification), UM-2270 (MBS modified with hydroxyl silicon), Quansheng Polycarbonate Technology Co., Ltd.

[0061] Lubricant: PETS-AHS, Italy Faji Co., Ltd.;

[0062] Antioxidants: Antioxidant 1076, Antioxidant 168, Beijing Jiyi Chemical Co., Ltd.;

[0063] High temperature resistant additive: S2200, rubber core particle size 120-160nm, epoxy grafted silicone acrylate core-shell polymer, Mitsubishi Rayon, Japan.

[0064] Embodiments 1 to 5

[0065] A method for preparing a crack-resistant, aging-resistant, high-light-shielding PC composite material comprises the following steps:

[0066] (1) Weigh the raw materials according to the mass fractions of PC resin, titanium dioxide, toughening agent, antioxidant, lubricant, and high temperature resistant additive in Table 1;

[0067] (2) The weighed raw materials of each component in step (1) are added to a high-speed mixer and mixed for 1.5 minutes, and then melt-extruded through a twin-screw extruder at a temperature of 220 to 240° C. and a screw speed of 350 rpm, and then cooled, dried, and granulated into pellets to obtain the product. The screw length-diameter ratio of the twin-screw extruder is 36:1.

[0068] Preparation of test standard samples: The modified plastic pellets were placed in a blast drying oven and dried at 120°C for 2 hours, and then molded by an injection molding machine to prepare test specimens and flat color plates. The performance test results of Examples 1 to 5 are shown in Table 2, and the cracking of the color plate is shown in Figure 1 .

[0069] Table 1 Weight parts of each raw material in Examples 1 to 5

[0070] Material composition Example 1 Example 2 Example 3 Example 4 Example 5 PC S1240T 94 92 90 93.5 90.5 UM-2270 2 4 6 4 4 CR210 3.5 3.5 3.5 2 5 PETS-AHS 0.2 0.2 0.2 0.2 0.2 1076 0.1 0.1 0.1 0.1 0.1 168 0.1 0.1 0.1 0.1 0.1 S2200 0.1 0.1 0.1 0.1 0.1

[0071] Table 2 Performance test results of Examples 1 to 5

[0072]

[0073] By comparing Example 1, Example 2 and Example 3, it can be seen that with the increase of the percentage of toughening agent UM-2270, the impact strength and impact strength of the PC composite material first increase and then decrease, the tensile strength and flexural strength gradually decrease, the transmittance has a downward trend, the melt mass flow rate is not much different, the toughening agent releases static tension stress in the matrix to induce plastic deformation in the matrix to absorb energy, and the formed holes can also induce a large number of silver streaks and shear bands to consume energy, but when the amount exceeds a certain amount, the induced silver streaks will densely merge into large cracks, resulting in material damage, so the toughening agent mass content is preferably controlled at 3%-5%, which can take into account both the shading performance and mechanical performance requirements.

[0074] By comparing Example 2, Example 4 and Example 5, it can be seen that as the percentage of titanium dioxide CR210 increases, the mechanical properties of the PC composite material gradually decreases and the light transmittance gradually decreases. Titanium dioxide has a very high refractive index and can significantly change the propagation direction of light. When the content of titanium dioxide increases, the scattering effect is enhanced, and the PC light-shielding effect will be better on a macro scale. However, when the titanium dioxide filling amount is too large, the distance between particles will become closer and easier to agglomerate in the matrix, thereby affecting the uniformity of product performance.

[0075] Depend on Figure 1 It can be observed that the color plates of Examples 1 to 5 crack, and it can be seen that the color plates of Examples 2 and 3 do not crack. Examples 1, 4, and 5 all have different degrees of cracking, among which Example 1 has a larger degree of cracking. It can be seen that during the shrinkage deformation process of PC injection molding, UM-2270 can guide the relaxation of PC molecular chains and reduce the residual thermal stress in the mold. Combined with the performance test results of each embodiment in Table 2, Example 2 is the best from the perspective of performance and surface morphology.

[0076] Comparative Examples 1 to 4

[0077] Comparative Examples 1 to 4 were respectively weighed according to the weight of each material in Table 3, and PC plastic pellets were prepared according to the method of step (2) of the above embodiment. The obtained modified plastic pellets were placed in a blast drying oven and dried at 120°C for 2 hours, and then molded by an injection molding machine to prepare test specimens and flat color plates. The performance test results of Comparative Examples 1 to 4 are shown in Table 4, and the cracking of the color plate is shown in Figure 1 .

[0078] Table 3 Weight parts of each raw material in Comparative Examples 1 to 4

[0079] Material composition Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PC-A1220 92 0 0 0 PC S1240T 0 92 92 0 PC1100-0000 0 0 0 92 M722 0 4 0 0 UM-2270 4 0 4 4 CR210 3.5 3.5 0 3.5 CR211 0 0 3.5 0 PETS-AHS 0.2 0.2 0.2 0.2 1076 0.1 0.1 0.1 0.1 168 0.1 0.1 0.1 0.1 S2200 0.1 0.1 0.1 0.1

[0080] Table 4 Performance test results of comparative examples 1 to 4

[0081] Test Item(Unit) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength(MPa) 56.37 55.28 52.27 57.69 Bending strength(MPa) 81.57 78.68 75.12 82.88 Flexural modulus (MPa) 2049.63 2016.28 2002.23 2063.71 <![CDATA[Izod impact strength of cantilever beam (KJ / m 2 )]]> 62.25 69.47 72.19 64.76 Melt mass flow rate (g / 10min) 21.26 13.71 12.93 13.21 Impact strength retention rate (%) 75 79 76 76 Light transmittance (%) 1.7 2.0 2.1 2.1

[0082] By comparing Example 2 with Comparative Example 1, it can be seen that the use of PC A1220 as the matrix resin significantly reduces the impact strength and impact strength retention of the PC composite material, and the light transmittance is slightly reduced. Low MFR PC has a higher molecular weight, which means that its molecular chains are longer and can be better entangled and combined with each other, so that the mechanical strength of the material is improved, and it can show better stability under long-term exposure to outdoor conditions. PC with a high melt index has good fluidity and consistency during processing, which can reduce the scattering and absorption of light, resulting in a decrease in light transmittance.

[0083] By comparing Example 2 with Comparative Example 4, it can be seen that the PC composite material containing siloxane groups has better impact strength retention and light-shielding performance when the base resin with the same melt index of 10 is selected. Siloxane groups form a protective barrier in the molecule, reducing the direct attack of UV on the PC molecular chain, effectively dispersing and blocking the propagation of light, and reducing the transmittance of light, thereby improving the material's aging resistance and light-shielding performance.

[0084] By comparing Example 2 with Comparative Example 2, it can be seen that under the same titanium dioxide filling ratio, the toughening agent UM-2270 is selected, the PC has better weather resistance and better mechanical properties than the PC composite material modified by M722. The silicon-oxygen bonds in UM-2270 are more compatible with the siloxane groups in the PC matrix, so that the toughening agent can be better dispersed in the PC matrix to form a uniform composite, reduce interface defects, and can effectively absorb and disperse stress, thereby improving the impact strength and impact strength retention rate of the material.

[0085] It can be seen from Example 2 and Comparative Example 3 that when titanium dioxide is selected as CR211 or CR210, the mechanical properties and melt mass flow rate of PC are not much different, but the impact strength retention rate of the PC composite material using titanium dioxide CR210 is better. CR211 with smaller particle size will aggregate due to the van der Waals force between particles, while CR210 with larger particle size will be more evenly dispersed in the matrix, with better UV shielding effect, ensuring the internal stability of PC and helping to extend the service life of PC.

[0086] Depend on Figure 1It can be observed that the color plates of Comparative Examples 1 to 4 all cracked to varying degrees, indicating that the type of toughening agent and the type of titanium dioxide will affect the synergistic effect of the two. The combination of UM-2270 and CR210 can ensure the dispersibility of the two in the matrix. The PC composite material prepared by using a resin with a melt index of 20 in Comparative Example 1 has serious surface cracking. This is because its melt strength is low and there are fewer entanglement points between the segments, resulting in relatively poor crack resistance. Stress cracking occurs under high-intensity alkaline damage or harsh environmental conditions. The resin melt indexes used in Example 2 and Comparative Example 4 are both 10. The color plate of Comparative Example 4 has a small degree of cracking, while no cracking is observed in Example 2. It can be seen that the siloxane copolymer PC has good melt ductility during processing, most of the segments are relatively easy to orient, and the internal residual stress is small.

[0087] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A crack-resistant, aging-resistant, high-light-shielding PC composite material, characterized in that: In terms of mass percentage, the raw material composition includes: PC resin 90%~94%, Titanium dioxide 2% to 6%, preferably 3% to 4%, more preferably 3.5%; Toughening agent 2% to 6%, preferably 3% to 5%, more preferably 4%; The PC resin is siloxane copolymerized PC; The toughening agent is hydroxy silicon modified methacrylic acid-butadiene-styrene copolymer.

2. The anti-cracking, aging-resistant and high light-shielding PC composite material according to claim 1, characterized in that: The PC resin has a melt flow rate of 10 to 15 g / 10 min at 300° C. and 1.2 kg, preferably 10 to 12 g / 10 min. The mass proportion of siloxane in the siloxane copolymer PC is 5% to 10%.

3. The anti-cracking, aging-resistant and high light-shielding PC composite material according to claim 1, characterized in that: The titanium dioxide is a rutile titanium dioxide pigment produced by the chloride process; The mass content of TiO2 in the titanium dioxide is above 95%, preferably above 96.5%; The particle size of the titanium dioxide is 200-250 nm, preferably 220-240 nm.

4. The anti-cracking, aging-resistant and high light-shielding PC composite material according to claim 1, characterized in that: The PC resin is S1240T produced by Wanhua Chemical Group Co., Ltd., and has a melt flow rate of 10 g / 10 min at 300° C. and 1.2 kg. The titanium dioxide is CR210 of CITIC Titanium Co., Ltd., with a particle size of 230nm and a mass content of TiO2 of 96.5%; The toughening agent is UM-2270 produced by QuanSheng Polycarbonate Technology Co., Ltd.

5. The anti-cracking, aging-resistant and high light-shielding PC composite material according to any one of claims 1 to 4, characterized in that: In terms of mass percentage, the raw material composition also includes: Lubricant 0.1%~0.3%, Antioxidant 0.1%~0.3%, High temperature resistant additive 0.1%~0.3%.

6. The anti-cracking, aging-resistant and high light-shielding PC composite material according to claim 5, characterized in that: The lubricant includes at least one of polyethylene wax, zinc stearate, and pentaerythritol stearate; The antioxidant is a compound of a main antioxidant and a secondary antioxidant, wherein the main antioxidant includes at least one of antioxidant 1098 and antioxidant 1076, and the secondary antioxidant includes at least one of antioxidant 168 and antioxidant 628; the mass ratio of the main antioxidant to the secondary antioxidant is 1:1; The high temperature resistant auxiliary agent comprises at least one of epoxy grafted silicon acrylate core-shell polymer and diaryl secondary amine composition.

7. The method for preparing the anti-cracking, aging-resistant and high light-shielding PC composite material according to any one of claims 1 to 6, characterized in that: include: The raw materials are mixed and then put into a twin-screw extruder for melting, mixing, plasticizing and extrusion to obtain the anti-cracking, aging-resistant and high light-shielding PC composite material.

8. The preparation method according to claim 7, characterized in that: The temperature of the twin-screw extruder is controlled at 220-240°C; The screw length-to-diameter ratio of the twin-screw extruder is 36 to 40:1; The main engine speed of the twin-screw extruder is 350-400 rpm.

9. Use of the anti-cracking, aging-resistant and high light-shielding PC composite material according to any one of claims 1 to 6 in the production of plastic-coated aluminum products.

10. The use according to claim 9, characterized in that: The plastic-coated aluminum product is a lamp structural component.